Optimal timing and arrangement for two-aircraft formations on North Atlantic under consideration of wind - Marks, Tobias; Swaid, Majed (AIAA Scitech 2020 Forum, 2020)
The aerodynamic formation flight is expected to enable high fuel savings for a trailing aircraft as the energy of the wake of a leading aircraft can be used to reduce the fuel burn. However, the extend of these benefits strongly depends on the routing of the aircraft especially if wind effects are taken into account. Within this work, the optimal formation tracks are estimated for two-aircraft formation missions, based on a westbound North Atlantic scenario with a set of representative weather patterns and several combinations of origin and destination airports. It will be shown, that the locations of the optimal rendezvous and separation points strongly vary with the wind fields and that clusters can be identified depending on the origins and destinations of the aircraft. The influence of the corresponding aircraft position in formation (follower or leader) on the benefits as well as the optimal departure time offset will be examined. Further it will be shown that, in order to simultaneously arrive at the optimal rendezvous points, a certain flexibility concerning the departure times is necessary. Average departure time offsets will be estimated.